ANALISIS POLITIK HUKUM DALAM FENOMENA PERCERAIAN DI LINGKUNGAN PEMERINTAH KABUPATEN TANAH DATAR : TINJAUAN TERHADAP KASUS PERSELINGKUHAN APARATUR SIPIL NEGARA - Naldi, Hasri; Elimartati, Elimartati (JURNAL HAKAM, 2024)
This paper aims to analyse politically and legally the phenomenon of divorce in Tanah Datar Regency, with a special emphasis on infidelity among state civil servants. This is due to the fact that divorce within the government is often a major concern in the legal and political context. Field research (Fiel Research) is a descriptive normative research methodology used in this writing. The data sources of this research consist of primary data sources and secondary data sources. The primary data source is the cause of divorce among state civil servants and the secondary data source is a book.The primary data source is the causes of divorce among state civil servants and the secondary data source is books and articles related to the factors that cause divorce among state civil servants. The results showed that the submission of divorce permits by civil servants in the Tanah Datar Regency government was due to family economic problems where the wife's income was greater than the wife's income. Family economic problems where the wife's income is greater than the husband's, disharmonious relationships between husband/wife, frequent arguments and indications that the husband/wife partner is having an affair. In the context of prevention efforts, the Regional Government of Tanah Datar Regency has issued Circular Letter Number 100.3.44-999-BKPSDM-2023 concerning Prohibition of Cheating for All ASN and PPNPN within the government of Tanah Datar Regency by visiting integrity and moral values in community life.